Imbrication de la mise en oeuvre concertée et solidaire du Traité sur les ressources phytogénétiques et du Protocole de Nagoya dans le conexte d’objetifs de politiques nationales plus larges: un atelier destine à des équipes nationales d’acteurs de politiques - ABS Capacity Development Initiative; Bioversity International (2016)
This report provides highlights from a workshop entitled “Embedding mutually supportive implementation of the Plant Treaty and the Nagoya Protocol in the context of broader national policy goals. A workshop for national teams of policy actors”. The workshop brought together eleven national teams comprised of National Focal Points for the Nagoya Protocol, the Plant Treaty and the GEF and representatives of lead national agencies dealing with climate change adaptation and agriculture and national finance and planning authorities. As the title of the workshop suggests, the participants examined options to embed the implementation of the Nagoya Protocol and the Plant Treaty in national programmess and strategies to promote climate change adaptation, poverty alleviation, food security and conservation. It was organized by the ABS Capacity Development Initiative and Bioversity International in cooperation with the African Union Commission and the Secretariats of the Convention on Biological Diversity and the International Treaty on Plant Genetic Resources for Food and Agriculture, held at the International Livestock Research Institute, Addis Ababa, Ethiopia, 16th – 20th November 2015